Neck management in patients with olfactory neuroblastoma. (February 2020) - Song, Xinmao; Huang, Chuang; Wang, Shengzi; Yan, Li; Wang, Jie; Li, Yi
Highlights: Cervical lymph metastasis is an independent factor contributing to poor survival. Cervical lymph node levels II and VIIa are most commonly involved. Treatment outcomes of N+ patients after systematic therapy remain unsatisfactory. Elective neck irradiation (ENI) reduces neck failure but does not improve survival. The value of ENI in patients with negative neck lymph nodes remains uncertain. Abstract: Objective: Optimal neck management in patients with olfactory neuroblastoma (ONB), a rare malignancy, remains uncertain. This study aimed to analyse patterns of cervical lymph node metastases and corresponding clinical outcomes and to investigate the value of elective neck irradiation (ENI) in this population. Methods and materials: This study retrospectively reviewed clinical records, imaging findings, nodal metastasis features and treatment data of 217 patients with ONB treated at our hospital during 1991–2019. Univariate and multivariate analyses were used to assess the influence of cervical lymph node involvement on treatment outcomes. Survival and regional failure rates were compared between patients with or without ENI. Results: Thirty-two patients (14.7%) presented initially with cervical lymph node metastases, most frequently at levels II (10.6%, 23/217) and VIIa (5.5%, 12/217). Patients with and without cervical node metastasis differed significantly in overall (OS) (41.9% vs. 86.1%, p < 0.001), progression-free (PFS) (41.9% vs. 84.8%, p < 0.001), regional failure-free (45.9% vs. 89%, p < 0.001) and distant metastasis-free survival (41.5% vs. 86.1%, p < 0.001). Cervical lymph involvement was an independent factor affecting poor OS (hazard ratio, 0.184, 95% confidence interval, 0.078–0.436, p < 0.001) and PFS (hazard ratio, 0.198, 95% confidence interval, 0.088–0.445, p < 0.001). Moreover, 43.8% patients (95/217) underwent ENI, which significantly reduced the incidence of regional recurrence from 10.7% to 3.2% ( χ 2 = 4.396, p = 0.036) but did not significantly affect other survival outcomes. Regional failures could be resolved using salvage treatment. Conclusions: Our findings indicate the importance of systematic therapy for patients with initial cervical lymph node metastases. ENI is not recommended for N0 disease.